A percepção do usuário quanto ao projeto padrão adotado na arquitetura escolar brasileira - Cordeiro, José Henrique (2021)
AbstractIn Brazil, at the beginning of the republican period, with the understanding of education as a tool for progress, the practice of creating school institutions based on a standard model emerged. The country’s industrialization process, together with the standardization of architecture, meant that the reproduction of standardized projects became common at the national level, based on the justification of development through the rationalization and standardization of construction. In the 1990s, the country implemented new social programs, one of them based on full-time education with a new pedagogical structure, materialized in the Comprehensive Centres for Child and Adolescent Care - CIACs - standard design schools designed by the architect João Filgueiras Lima. In 1992, the program that originated the CIAC schools were changed and this model institution was renamed CAIC - Comprehensive Care Centre for Children and Adolescents, with few changes in its architectural design and maintaining the same pedagogical program already in use. Through a case study in the Pelotas CAIC, in which interviews were conducted with school teachers to understand their perception of a school with standard architecture, this article presents the CAICs and their history, as well as deals with the appropriation and identity formation of users in the context of the standard project. The work shows that this type of performance already puts the future building subject to probable interventions so that the user can remedy the problems arising from the lack of participatory planning in the design phase of the school.